Scientific Study of Cooling of Hydrotherm Extracted from the Source when Heating Buildings with Renewable Hydrotherm in the District of Guzor - Erjan Kahya; Makhmudov Said Makhmudovich; Kambarov Makhsudali Makhmudalievich; Baymatov Shaxriddin Xushvaqtovich; Rakhimov Sherzod Abduvaxobjonovich; Tulyaganov Zafar Sunnatovich (Scientific Trends, 2024)
This article presents the method of heating buildings from hydrotherms available in the territory of Uzbekistan, as well as the calculation methodology and calculation results of the hydrothermal temperature drop extracted from the source.
Keywords: Renewable energy, geothermal energy, biosphere, energy efficient foundation, Earth's core, Earth's crust, hydrothermal district heating system.